2003
DOI: 10.1001/archinte.163.8.936
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Prediction Rule to Identify Patients With Atrial Fibrillation and a Low Risk for Stroke While Taking Aspirin

Abstract: Irrespective of age, patients with AF and none of these 4 clinical features and who take aspirin have stroke rates comparable to those of age-matched community cohorts and would not benefit substantially from anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(74 citation statements)
references
References 43 publications
1
67
0
6
Order By: Relevance
“…11 -13 Van Walraven et al also analyzed data from 6 small clinical trials and found that myocardial infarction was significantly associated with stroke. 12 In AF patients, the observed rate of stroke was 5.6 per 100 person-years in patients with a history of myocardial infarction or angina pectoris and only 1.4 in patients without a history of myocardial infarction or angina pectoris. 12 In alignment, Aronow et al found that a history of myocardial infarction was associated with an odds ratio of 4.8 for thromboembolic stroke.…”
Section: Vascular Disease and Stroke Risk In Atrial Fibrillationmentioning
confidence: 93%
See 2 more Smart Citations
“…11 -13 Van Walraven et al also analyzed data from 6 small clinical trials and found that myocardial infarction was significantly associated with stroke. 12 In AF patients, the observed rate of stroke was 5.6 per 100 person-years in patients with a history of myocardial infarction or angina pectoris and only 1.4 in patients without a history of myocardial infarction or angina pectoris. 12 In alignment, Aronow et al found that a history of myocardial infarction was associated with an odds ratio of 4.8 for thromboembolic stroke.…”
Section: Vascular Disease and Stroke Risk In Atrial Fibrillationmentioning
confidence: 93%
“…12 In AF patients, the observed rate of stroke was 5.6 per 100 person-years in patients with a history of myocardial infarction or angina pectoris and only 1.4 in patients without a history of myocardial infarction or angina pectoris. 12 In alignment, Aronow et al found that a history of myocardial infarction was associated with an odds ratio of 4.8 for thromboembolic stroke. 13 The NICE (National Institute for Health and Clinical Excellence) guidelines systematic review did conclude that prior myocardial infarction was a stroke risk factor in AF.…”
Section: Vascular Disease and Stroke Risk In Atrial Fibrillationmentioning
confidence: 93%
See 1 more Smart Citation
“…Kliniczne skale ryzyka udaru mózgu i zatorowości w krążeniu systemowym Proste, dające się wykorzystywać w praktyce klinicznej schematy stratyfikacji ryzyka udaru mózgu u pacjentów z AF opracowano pod koniec lat 90. XX wieku w małych badaniach kohortowych, a później udoskonalono je i poddano walidacji w większych populacjach [364][365][366][367][368]. Wprowadzenie skali CHA 2 DS 2 -VASc (tab.…”
Section: Przewidywanie Ryzyka Udaru Mózguunclassified
“…This patient had a relative high risk of recurrent stroke because her CHADS2 index was 4 with age 75 years or older, prior stroke history, heart failure [8]. The stroke rate per 100 patient-years is 8.5 (95% CI, 6.3-11.1) for a score of 4 [9].…”
Section: Discussionmentioning
confidence: 98%